The cosmopolitan subject and the question of cultural identity: The case of Crime and Punishment. (April 2017) - Spector, Hannah
Though contemporary discourse on cosmopolitanism has celebrated a cosmopolitan subject's "rootedness" in two worlds – i.e. the polis and the cosmos – this emphasis has evaded analysis of the historical and damning term "rootless cosmopolitan." Under the totalitarianisms of Nazism and late Stalinism, a "rootless cosmopolitan" was a life-threatening epithet aimed at those people, namely "the Jews, " criminalized for supposedly lacking national allegiance and affiliating with foreign cultures. This paper argues that an ethical problem arises when cosmopolitanism is understood in cultural terms. To illuminate this problem in the particular, this paper interprets Dostoevsky's Crime and Punishment, specifically the novel's nationalistic themes and its cosmopolitan villain, Peter Petrovich Luzhin. In the unfolding analysis that draws from scholarship in cultural criminology, it is revealed that the Russian writer's designated masterful genius helped fuel one of the greatest crimes in history (the Holocaust) perpetrated against a people accused of cosmopolitanism. It is argued that interpreting the criminalization of Luzhin provides an allegorical occasion to gain conceptual clarity on present articulations of cosmopolitanism as a cultural construct. Attending to Dostoevsky's anti-cosmopolitanism, and those whom he has in/directly influenced on this subject, provides a rationale for critiquing cultural cosmopolitanism – a construct that is conceptually and materially dangerous.